REE geochemistry and fluid-inclusion studies of fluorite deposits from the Yaylagozu area (Yildizeli-Sivas) in Central Turkey - Sasmaz, Ahmet; Yavuz, Fuat (E Schweizerbartsche Verlagsbuchhandlung, 2007)
Skarn- and vein-type fluorite deposits in the vicinity of Yaylagozu, Yildizeli-Sivas, are found within the syenites and their skarn zones that are located in the Central Anatolia Massif. Mining was activite on several fluorite mineralizations during the early 1950 s, but is presently inactive. The goal of this study, on the basis of REE geochemistry and fluid inclusion investigations, is to explain the genesis and physicochemical conditions of fluorite mineralization hosted by calc-alkaline to alkaline syenites of Upper Cretaceous age. The rare-earth element content of the Yaylagozu fluorite is quite variable. Fluorites have moderate to high total REE contents ranging from 68 ppm to 5288 ppm, with a mean of 907, compared with the fluorite occurrences elsewhere both in hydrothermal and sedimentary origin. Light rare-earth elements (LREE) are enriched in all the studied fluorite samples. Chondrite-normalized La/Lu ratios range from 13.7 to 364, regardless of color variation in fluorites. This, as well as low Tb/La ratio, is the indicative of early crystallization of fluorite from the mineralizing solution. The Tb/La and Tb/Ca ratios of fluorites in the present study indicate that they plot mainly in the pegmatitic or high-hydrothermal field of the diagram Of MOLLER et al. (1976) with the characteristics of primary crystallization and remobilization trends. Fluid inclusion microthermometry indicates that the fluorite in most of the veins was formed from the fluids at temperatures between 161 degrees and 243 degrees C. Primary fluid inclusions for samples plotting into the pegmatitic field of the MOLLER et al. diagram (1976) has the highest homogenization temperatures.
Keywords: fluorite; fluid inclusion; REE; skarn; syenite; vein; Central Anatolia; Yaylagozu